Quality Of Life In Malaysian Small Town: Antecedent of The Major Determinants - Hussin, Nor Syahira; Muhamad Nazor, Nur' Aqilah; Mohamad, Zuraida; Mansor, Norudin (SOTVI, 2019)
Â This paper attempts to discuss the findings based on the survey on therelationship between determinants that reflected their influence on thequality of life among the residents living in a small town nearby one ofthe largest oil based manufacturing industries in Malaysia. Samples ofthe study were represented among those residents from the teenagers upto the old population categories. For ensuring an appropriaterepresentation and adequate generalization, 306 questionnaires weredistributed in urban and rural area. While analyzing the relationship aswell as its impact, the study also examined possibility of differencesbetween several selected profiles with the quality of life. In order to getmore generalization from the pool of respondents, the further study maydo deeper analysis such as focus in sub group respondents, besidesobserving samples in a much larger group from other town or cities inMalaysia.